Making waves: Wastewater surveillance of SARS-CoV-2 in an endemic future. (1st July 2022) - Wu, Fuqing; Lee, Wei Lin; Chen, Hongjie; Gu, Xiaoqiong; Chandra, Franciscus; Armas, Federica; Xiao, Amy; Leifels, Mats; Rhode, Steven F; Wuertz, Stefan; Thompson, Janelle; Alm, Eric J
Highlights: WBS will be a feasible tool to monitor SARS-CoV-2 in an endemic future. Objectives of WBS will shift to indicate the trend of viral infection in population. WBS and clinical testing can be integrated for cost-effective mass surveillance. WBS data needs to be optimized to improve epidemiological inference. WBS methods developed in context of SARS-CoV-2 is invaluable for future pandemics. Abstract: Wastewater-based surveillance (WBS) has been widely used as a public health tool to monitor the emergence and spread of SARS-CoV-2 infections in populations during the COVID-19 pandemic. Coincident with the global vaccination efforts, the world is also enduring new waves of SARS-CoV-2 variants. Reinfections and vaccine breakthroughs suggest an endemic future where SARS-CoV-2 continues to persist in the general population. In this treatise, we aim to explore the future roles of wastewater surveillance. Practically, WBS serves as a relatively affordable and non-invasive tool for mass surveillance of SARS-CoV-2 infection while minimizing privacy concerns, attributes that make it extremely suited for its long-term usage. In an endemic future, the utility of WBS will include 1) monitoring the trend of viral loads of targets in wastewater for quantitative estimate of changes in disease incidence; 2) sampling upstream for pinpointing infections in neighborhoods and at the building level; 3) integrating wastewater and clinical surveillance for cost-efficient population surveillance; and 4) genome sequencing wastewater samples to track circulating and emerging variants in the population. We further discuss the challenges and future developments of WBS to reduce inconsistencies in wastewater data worldwide, improve its epidemiological inference, and advance viral tracking and discovery as a preparation for the next viral pandemic. Graphical abstract: Image, graphical abstract